Determinants of non-performing loans : a panel data approach - Ferreira, Cândida (2022)
This paper analyses the evolution of the bank non-performance loans to total loans ratio using three categories of explaining variables: bank performance indicators (bank credit to bank deposits ration, bank cost to income ratio, bank net interest margin, bank noninterest income to total income, and bank return on assets), market conditions and financial structure indicators (bank concentration, Lerner index, bank Z-score, bank regulatory to risk-weighted assets, and bank crisis dummy), and economic growth indicator (natural logarithm of real GDP per capita). The paper applies panel fixed effects and dynamic Generalised Method of Moments (GMM) estimates to a panel of 80 countries spread by all Continents, over the period 1999-2017. The results obtained clearly demonstrate that bank performance, bank market conditions, and bank capital regulation are relevant to explain the evolution of non- performance loans, but the promotion of economic growth is always much more important to assure the decrease the levels of non-performing loans, preventing the losses of the banking system as well as potential financial crisis.